Gordon Parks : born Black : a personal report on the decade of Black revolt, 1960-1970 - Parks, Gordon, 1912-2006 (Steidl ; Gordon Parks Foundation, 2024)
"Originally published in 1971, Gordon Parks' Born Black was the first book to unite his writing and his photography and also the first to provide a focused survey of Parks' documentation of a crucial time for the civil rights and Black Power movements. More than 50 years later, this expanded edition illuminates Parks' vision for the book and offers deeper insight into the series contained within. The original publication featured nine articles commissioned by Life magazine from 1963 to 1970 supplemented with later commentary by Parks and presented as his personal account of these important historical moments. Born Black includes the original text and images, as well as additional photographs from each series, spreads from the 1971 book, early correspondence and reproductions of related Life articles. The nine series included in Born Black include a rare glimpse inside San Quentin State Prison; extensive documentation of the Black Muslim movement and the Black Panthers; his commentaries on the deaths of civil rights leaders Malcolm X and Martin Luther King, Jr.; intimate portrait studies of Stokely Carmichael, Muhammad Ali and Eldridge Cleaver; and a narrative of the daily life of the impoverished Fontenelle family in Harlem. These selections have come to define Parks' legendary career as a photographer and activist. This reimagined, comprehensive edition of Born Black highlights the lasting legacy of these projects and their importance to our understanding of critical years in American history." --